Entrepreneurial Competence Affecting Competitive Advantages Through Thai-Laos Border Trade Policy: A Case Study of Huai Kon Border Chaloem Phrakiat District, Nan Province - Rakjul, Ponkrit (Modern Management Frontier Journal, 2024)
This article aims to study (1) the performance of Thai-Lao border trade entrepreneurs, (2) border trade policies that support Thai-Lao border trade entrepreneurs, (3) the competitive advantage of Thai-Lao border trade businesses, and (4) the impact of border trade policy on entrepreneurs' performance, affecting competitive advantage. This is a quantitative study with a population and sample group consisting of 300 border trade entrepreneurs in Chalerm Phra Kiat District, Nan Province, using a questionnaire. The research findings revealed that (1) the performance of Thai-Lao border trade entrepreneurs was high (mean = 3.65), (2) border trade policies supporting Thai-Lao border trade entrepreneurs were rated high (mean = 3.85), (3) the competitive advantage of Thai-Lao border trade businesses was high (mean = 3.88), and (4) the performance of entrepreneurs and border trade policy had a positive direct impact on competitive advantage. The performance of entrepreneurs had a direct positive impact on border trade policy with a direct effect size of 0.77 and a total effect size of 0.77, statistically significant at the 0.01 level. Border trade policy had a direct positive impact on competitive advantage with a direct effect size of 0.96 and a total effect size of 0.96, statistically significant at the 0.01 level. Entrepreneur performance had a direct positive impact on competitive advantage with a direct effect size of 0.25, statistically significant at the 0.01 level, and also had an indirect positive effect on competitive advantage through border trade policy, with an indirect effect size of 0.65 and a total effect size of 0.90, statistically significant at the 0.01 level. For the prediction coefficient (R2) of the latent variable structural equation model, the R^2 of border trade policy was 0.60, indicating that the variables in the model explained 60% of the variance in border trade policy. The R^2 of competitive advantage was 0.84, indicating that the variables in the model explained 84% of the variance in competitive advantage.